Characterization of Pulmonary Emboli in Total Joint Arthroplasty Patients Compared to General Medical Patients - Jové, Nathaniel A.; Samaan, Sam; Pizzimenti, Natalie M.; Lincoln, Denis; Markel, David C. (The Journal of Knee Surgery, 2019)
Pulmonary emboli (PEs) occur in medical and postoperative total joint arthroplasty (TJA) patients. These are different patient populations, yet both undergo identical diagnosis and treatment regardless of PEs size and quantity. To date, there has been no analysis of the location, size, and quantity of emboli that occur postoperatively in TJA compared with general medical patients. We hypothesized TJA patients would have different size and distribution of PEs per event compared with medical patients. A retrospective chart review was conducted of patients who underwent total hip or knee arthroplasty in comparison to general medical patients at our institution from 2006 to 2011 with a PE diagnosis. Medical co-morbidities, sex, age, procedure, postoperative day, size, and location of PE using spiral computed tomography were recorded using a novel mapping scheme. Embolus size was defined based on blockage level in the pulmonary arterial tree. Of the 4,178 TJA patients reviewed, 51 were diagnosed with a PE. A total of 67% of TJA patients were women, yet women represented 90% (n = 46) of TJA PE patients (p < 0.0001). Medical patients had an equal distribution of men and women with PEs. Orthopaedic patients averaged more (4.0 vs. 2.2, p < 0.0001) and smaller PEs compared with medical patients (p < 0.0001). In conclusion, women undergoing TJA had significantly higher risk of developing PE compared with male arthroplasty or medical patients. Differences were observed in size and distribution of PEs between medical and TJA patients, which suggest a different nature of embolic phenomenon.
Keywords: pulmonary emboli; postoperative; total joint arthroplasty; general medical patients; computed tomography